Filmowa półka sezonu 2012/2013. Część II - Tambor, Agnieszka (Postscriptum Polonistyczne, 2020)
This article presents the second part of the summary of the season 2011/2012 of Polish filmmaking. The following films are decribed here: 80 milionów dir. Waldemar Krzystek; Big Love dir. Barbara Białowąs; Hans Kloss. Stawka większa niż śmierć dir. Patryk Vega; Imagine dir. Andrzej Jakimowski; Jesteś Bogiem dir. Leszek Dawid; Lęk wysokości dir. Bartosz Konopka; Mój rower dir. Piotr Trzaskalski; Nad życie dir. Anna PluteckaMesjasz; Obława dir. Marcin Kryształowicz; Paths of Hate dir. Damian Nenow; Pokłosie dir. Władysław Pasikowski; Róża dir. Wojciech Smarzowski; Rzeź dir. Roman Polański; Supermarket dir. Maciej Żak. The author concentrates mainly on the premieres for the second half of the year 2012. All the movies that are described in the article are presented from the perspective of how interesting they would be to a foreigner or a person who studies Polish as a foreign language.